1994
DOI: 10.1016/s0006-3495(94)80876-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of cardiac structure by mechanical feedback in the environment of the cell: a model study

Abstract: In the cardiac left ventricle during systole mechanical load of the myocardial fibers is distributed uniformly. A mechanism is proposed by which control of mechanical load is distributed over many individual control units acting in the environment of the cell. The mechanics of the equatorial region of the left ventricle was modeled by a thick-walled cylinder composed of 6-1500 shells of myocardial fiber material. In each shell a separate control unit was simulated. The direction of the cells was varied so that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 45 publications
(40 reference statements)
4
67
0
1
Order By: Relevance
“…First, from computer simulation and animal model, Arts et al 6 found that helical fiber orientation was a result of mechanical feedback making the fiber stress and/or strain more uniform across the wall; therefore, it would be of mechanical benefit to restore the (LHF% ϩ RHF%)/CF% ratio during the healing process of MI. Second, it is known that wall stress is greater at the subendocardial surface than the subepicardial surface of the heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, from computer simulation and animal model, Arts et al 6 found that helical fiber orientation was a result of mechanical feedback making the fiber stress and/or strain more uniform across the wall; therefore, it would be of mechanical benefit to restore the (LHF% ϩ RHF%)/CF% ratio during the healing process of MI. Second, it is known that wall stress is greater at the subendocardial surface than the subepicardial surface of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 This structure is a key determinant of ventricular mechanical properties, including torsion, strain, and stress, 3,4 Clinical Perspective 1045 and structure adaptation. 5,6 From a clinical point of view, understanding the altered tissue integrity and fiber architecture in diseased myocardium such as myocardial infarction (MI) is critically important because it might shed light on the mechanism of structure-function remodeling after MI. However, conventional histological study of myocardial fiber architecture is time-consuming and destructive and can be done in the excised heart only.…”
mentioning
confidence: 99%
“…Similarly, from the biomechanical standpoint, torsional deformation increases ventricular mechanical efficiency by generating high ventricular pressure and a large ventricular ejection volume, while reducing the gradients of LV transmural fiber strain and oxygen consumption. 34,35 Thus, it has been demonstrated that torsional deformation is a sensitive indicator of LV function. Global LV systolic function has been shown to be impaired in ASD [8][9][10]36,37 and we also found that the LVEF in patients with ASD was lower than that of normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…The same idea was applied to force generation: it is expected to be uniform, and mechanical models have been developed that support this concept. 25,26 Microsphere flow studies by Hoffman et al 27,28 and our own laboratory (Yipintsoi et al 1 and subsequent studies, including Bassingthwaighte et al 2 ) demonstrated that the flow heterogeneity was consistently large, and comparisons with molecular microspheres removed all doubt that the magnitude of the variance of the flows might have been attributable to peculiarities of distribution of particulate spheres, 2 and led to the conclusion that the heart was regionally heterogeneous metabolically. A clear message came from the low-flow regions in the normal heart: these regions did not receive enough oxygen, even at 100% extraction, to metabolize at the average rate for the whole left ventricle.…”
Section: Oxygen Consumptionmentioning
confidence: 93%